2018
DOI: 10.3233/sw-180300
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning approach for product matching and categorization

Abstract: Consumers today have the option to purchase products from thousands of e-shops. However, the completeness of the product specifications and the taxonomies used for organizing the products differ across different e-shops. To improve the consumer experience, approaches for product integration on the Web are needed. In this paper, we present an approach that leverages deep learning techniques in combination with standard classification approaches for product matching and categorization. In our approach we use str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 33 publications
0
46
0
2
Order By: Relevance
“…Moreover, the random forest model gives very good results on all three datasets. With that said, it is to be expected to have better results for both decision tree and random forest with a better feature extraction model as proven in Ristoski et al [42].…”
Section: Product Matching Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, the random forest model gives very good results on all three datasets. With that said, it is to be expected to have better results for both decision tree and random forest with a better feature extraction model as proven in Ristoski et al [42].…”
Section: Product Matching Resultsmentioning
confidence: 95%
“…Finally, in [41], the authors compare various classifiers for product resolution (SVMs, Random Forest, Naive Bayes) with features extracted from a dictionary method and multiple Conditional Random Fields (CRFs) models. The authors, extended their work in [42], where they present extraction models with latent continuous features for product matching and classification, proving that more sophisticated feature extraction methods significantly improve traditional machine learning methods for entity resolution.…”
Section: Related Workmentioning
confidence: 95%
“…They indicated that performance could be improved further using a method that deletes noise data as stopwords. The related works mentioned above regard automatic product classification as a classification problem [19]. Furthermore, a commonality between these works is that they discussed the effect of various input data on classification models.…”
Section: Related Workmentioning
confidence: 99%
“…There are wide range of matching algorithms studied from various string matching (Vandic et al, 2012;Thor, 2010) to more advance methods. We refer the reader to Ristoskia et al (2017) and Kannan et al (2011) for a good brief overview of these studies.…”
Section: Related Workmentioning
confidence: 99%